EFEKTIFITAS PEMBELAJARAN IPA MELALUI METODE INSIDE-OUTSIDE-CIRCLE TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA - Baisa, Hidayah; ., Verawati (ATTA`DIB, 2015)
The aim of the research is to know the effectivity of Inside-Outside-Circle method, the achievement and both corelation to science (IPA) lesson in MI Mathla’ul Anwar 2, North of Bogor. This study conducted field research. The results of the research are; the application of the method is quitely good and reached 60,97 %, and also the achievements reached 73,91 %. It can be concluded that learning science (IPA) using Inside-Outside-Circle method to the increasing the achievement of students is effective and positive. This can be seen from amount rxy = 0,752 bigger than table r (range of significance 5% = 0,361).